Independent Learning Through Instructional Videos and Text-Based Materials: Effects on Students’ Conceptual Understanding of Chemistry - Ricardus Jundu; Silfanus Jelatu; Eufrasia Jeramat; Lana Sugiarti (UIN Fatmawati Sukarno Bengkulu, 2026)
This study examines the effectiveness of chemistry instructional videos in enhancing students’ conceptual understanding within an independent learning context. A quasi-experimental design employing a non-equivalent control group was adopted. The sample comprised 76 undergraduate students enrolled in the Agribusiness Program at Universitas Katolik Indonesia Santu Paulus Ruteng during the 2022/2023 academic year, consisting of an experimental group (n = 39) and a control group (n = 37). The experimental group engaged in independent learning supported by short, topic-based chemistry instructional videos, whereas the control group utilized text-based instructional materials. The videos were designed as narrated audiovisual modules containing concept visualizations, worked examples, pause-and-reflect prompts, and brief LMS-based formative questions, with each video lasting approximately 8–12 minutes. Students’ conceptual understanding was measured using an essay-based posttest instrument, and data were analyzed through descriptive statistics, assumption testing, an Independent Samples t-test, and Cohen’s d effect size using SPSS version 22. The results indicated a statistically significant difference between the two groups (t(74) = 2.66, p = 0.010), with students in the experimental group demonstrating higher conceptual understanding than those in the control group. The effect size (Cohen’s d = 0.61) indicated a medium practical effect. These findings provide empirical evidence for the effectiveness of video-based learning in chemistry education, particularly in supporting self-regulated learning and bridging conceptual gaps among students from diverse educational backgrounds.